2016
DOI: 10.1002/2016gl068977
|View full text |Cite
|
Sign up to set email alerts
|

Methane fluxes from the sea to the atmosphere across the Siberian shelf seas

Abstract: The Laptev and East Siberian Seas have been proposed as a substantial source of methane (CH4) to the atmosphere. During summer 2014, we made unique high‐resolution simultaneous measurements of CH4 in the atmosphere above, and surface waters of, the Laptev and East Siberian Seas. Turbulence‐driven sea‐air fluxes along the ship's track were derived from these observations; an average diffusive flux of 2.99 mg m−2 d−1 was calculated for the Laptev Sea and for the ice‐free portions of the western East Siberian Sea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
121
1

Year Published

2016
2016
2017
2017

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 107 publications
(138 citation statements)
references
References 55 publications
(71 reference statements)
12
121
1
Order By: Relevance
“…For the North Sea in winter, much higher values were obtained (7-62 cm h −1 = 17-150 m d −1 ) (Nightingale et al, 2000). Similar values were reported for a bay in the Baltic Sea, at around 7 cm h −1 = 17 m d −1 (Silvennoinen et al, 2008), but lower values were reported for a Japanese estuary in summer (0.69-3.2 cm h −1 = 1.7-7.7 m d −1 ) (Tokoro et al, 2007). Our values for k 600 ranged from 0.37 to 3.17 m d −1 , with a median of 1.05 m d −1 .…”
Section: Diffusive Methane Fluxsupporting
confidence: 63%
“…For the North Sea in winter, much higher values were obtained (7-62 cm h −1 = 17-150 m d −1 ) (Nightingale et al, 2000). Similar values were reported for a bay in the Baltic Sea, at around 7 cm h −1 = 17 m d −1 (Silvennoinen et al, 2008), but lower values were reported for a Japanese estuary in summer (0.69-3.2 cm h −1 = 1.7-7.7 m d −1 ) (Tokoro et al, 2007). Our values for k 600 ranged from 0.37 to 3.17 m d −1 , with a median of 1.05 m d −1 .…”
Section: Diffusive Methane Fluxsupporting
confidence: 63%
“…Thornton et al . [] described a continuous shipboard survey of CH 4 concentrations in the atmosphere and near‐surface waters in much of this same area. They conclude that ebullition does not substantially contribute to the sea‐air CH 4 flux, which they calculate to be less than 2.9 Tg yr −1 CH 4.…”
Section: Climate Susceptibility Of Gas Hydrates By Physiographic Provmentioning
confidence: 99%
“…Investigations led by Shakhova et al (2010Shakhova et al ( , 2014 estimated total ESAS emissions from diffusion, ebullition, and storm-induced degassing, at 8-17 TgCH 4 yr −1 . A subsequent measurement campaign led by Thornton et al (2016a), though not made during a stormy period, failed to observe the high rates of continuous emissions reported by Shakhova et al (2014), and instead estimated an average flux of 2.9 TgCH 4 yr −1 . Berchet et al (2016) also found that such values were not supported by atmospheric observations, and instead suggested the range of 0.0-4.5 TgCH 4 yr −1 .…”
Section: Introductionmentioning
confidence: 99%